PROMOTION OF THE BUSINESS ENTREPRENEURSHIP AND UNIVERSITY PROFESSIONAL TRAINING: CENTER FOR ENTREPRENEURSHIP IN THE FACULTY OF ADMINISTRATIVE SCIENCES, UNMSM - Bouby Tolentino, Francisca (2014)
This study highlights the need to promote an enterprising attitude on university professional training in an less developed country as Peru, with an primary exported economic structure where most of employment is explained by small and medium enterprises, which shows the imperative of an high aggregate value employment. So, by promoting the undertaking amongst future graduates is considered one of the highest goals of the Peruvian university system, and this reveals the needing of an educational public policy that encourage educational development in all levels, with emphasis on research, innovation and enterprising attitude.